Sources of knowledge and process innovation: The moderating role of perceived competitive intensity - Aliasghar, Omid; Rose, Elizabeth L.; Asakawa, Kazuhiro (International Business Review, 2022)
•We examine the relationship between knowledge search and process innovation by domestic firms in a country subject to economic sanctions.•The empirical analysis uses data on 171 Iranian automobile component suppliers.•External knowledge search from foreign partners has a positive impact on process innovation by the component suppliers.•The perceived competitive intensity in the domestic markets strengthens the impact of foreign partners on process innovation. Global competition means that firms are under pressure to systematically develop the efficiency of their manufacturing processes. However, little has been said in the international business literature about how firms, especially those subject to severe barriers, can search for knowledge within and across national boundaries to help in the development of process innovation. We build on key aspects of the innovation and search strategy literature to develop our conceptual model and hypotheses, which we test in the context of a less-developed, isolated, and closed economy, using data from 171 automotive component suppliers in Iran. We find that foreign knowledge search is positively related to process innovation, even in an economy that operates under severe economic sanctions. This contributes to the international business field by providing evidence that, while economic sanctions are increasingly used in modern geopolitics by the world’s most powerful countries, these actions may fail to achieve their goals with respect to individual businesses.